THE EFFECT AUGMENTED REALITY BASED POCKET BOOK MEDIA ON STUDENTS' KNOWLEDGE ABOUT ANEMIA - Lailiyana, Lailiyana; Sartika, Yan; yanti, Yanti (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
One of the health problems of young women is iron deficiency anemia. As many as 19.4% of adolescents aged 15-24 years in Riau Province suffer from anemia (Norlita et al., 2023). This study aims to determine the effect of education using augmented reality (AR)-based pocket book media on female students' knowledge about anemia in young women. The type of quantitative research with a quasi-experimental design. The study population was all 124 female students of class XII IPS with a sample of 37 people taken using the purposive sampling technique. The data collection method was the observation method. Data analysis used the dependent t-test (95% confidence interval). The results of the study showed that there was an increase in the average score of female students' knowledge about anemia from 8.43 (SD = 1.259) to 9.65 (SD = 0.676) after education. AR-based media improves female students' understanding of anemia because this technology makes unclear objects look more real when felt (Suryaningsih, 2020). Statistically, there is an effect of providing education using AR-based pocket book media on female students' knowledge about anemia in adolescent girls (p=0.000).